The Arielistas facing the indigenous problem 1900-1930 - Gonzales Alvarado, Osmar (1989)
Usually, when we address the problem of the Indian, and with it the problem of agriculture, we turn to authors considered "classics" who, without a doubt, have profoundly marked the evolution of social ideas in Peru. Names like Valcárcel, Castro Pozo, García, Escalante, Mariátegui himself, live quickly in our memory and we immerse ourselves in his works. However, and even when we recognize the positive that the national culture contains having some references that function as symbols, we have to regret at the same time that other authors, equally concerned with the great national problems, are forgotten or, worse still, by not reading them, they are locked into stereotypes that, because they are such, do not contribute to fully understanding them.